A Collaborative Study to Establish an International Standard for Alpha-Thrombin - Gaffney, P J; Heath, A B; Fenton II, J W (Thrombosis and Haemostasis, 1992)
Since 1975 an International Standard for Thrombin of low purity has been used. While this standard was stable and of value for calibrating thrombins of unknown potency the need for a pure a-thrombin standard arose both for accurate calibration and for precise measurement of thrombin inhibitors, notably hirudin. An international collaborative study was undertaken to establish the potency and stability of an ampouled pure a-thrombin preparation. A potency of 97.5 international units (95% confidence limits 86.5-98.5) was established for the new a-thrombin standard (89/ 588) using a clotting-assay procedure. Stability data at various elevated temperatures indicated that the standard could be transported and stored with no significant loss of potency.Ampoules of lyophilised a-thrombin (coded 89/588) have been recommended as an International Standard for a-thrombin with an assigned potency of 100 international units per ampoule by the International Society for Thrombosis and Haemostasis (Thrombin and its Inhibitors Sub-Committee) in Barcelona, Spain in July 1990 while the Expert Committee on Biological Standardisation and Control of the World Health Organisation will consider its status at its next meeting in Geneva in 1991.